Iron-based amorphous alloy with low coercive force, high ductility and toughness and strong forming ability and preparation method

By optimizing the elemental composition ratio of iron-based amorphous alloys and combining the interaction and synergistic effects between elements, the problems of high coercive force, saturated magnetic induction strength, amorphous formation ability and toughness are solved, and the problem of insufficient coercive force of iron-based amorphous alloys is achieved. Iron-based amorphous alloy with low coercivity, high saturation magnetic induction strength and high ductility toughness.

CN119433386APending Publication Date: 2025-02-14TSINGHUA UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310960957.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-01
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The coercive force of existing iron-based amorphous alloys is difficult to reduce, and the saturated magnetic induction strength, amorphous formation ability and ductility need to be improved.

Method used

By studying the interaction and synergistic effects between elements, the general formula of an iron-based amorphous alloy is provided as FeaBbCcSidPeMf, where a, b, c, d, e, and f are the atomic percentages of each element, M is V, 0≤ f≤0.8, d>e, 0.13≤b/a≤0.17, d+e≤c or 4.0≤c+d+e≤5.0, optimize the element composition ratio to improve the amorphous formation ability and soft magnetic properties of the alloy.

Benefits of technology

Iron-based amorphous alloy with low coercive force, high saturation magnetic induction strength, high ductility toughness and strong formation ability, with saturated magnetic induction strength ≥1.66T, coercive force ≤1.0A/m, amorphous formation ability and bending toughness Significant improvement.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119433386A_ABST
    Figure CN119433386A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of magnetic metal material preparation, and particularly relates to an iron-based amorphous alloy with low coercive force, high ductility and toughness and strong forming ability and a preparation method. The iron-based amorphous alloy has a general formula of Fe B C < c > S < d > P < e > M < f >, wherein M is V; 0 < = f < = 0.8; d > e; 0.13 < = b / a < = 0.17; d + e < = c; or 4.0 < = c + d + e < = 5.0. The saturation flux density of the iron-based amorphous alloy is larger than or equal to 1.66 T or the magnetic induction intensity B800 under the condition of 800 A / m is larger than or equal to 1.65 T, the coercive force after annealing is smaller than or equal to 1.0 A / m, and the iron-based amorphous alloy has high amorphous forming ability and bending toughness. The iron-based amorphous alloy provided by the invention has high saturation flux density, low coercive force and low iron loss. The iron-based amorphous alloy does not contain precious metal elements, easy-to-oxidize elements and high-melting-point elements, is low in cost, has low requirements on industrial equipment and is beneficial to industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of magnetic metal material preparation, and specifically relates to an iron-based amorphous alloy having low coercivity, high ductility and strong forming ability and a preparation method thereof. Background Art

[0002] With the development of strategic emerging industries such as new energy vehicles, intelligent manufacturing, rail transportation, and aerospace, modern technology requires motors to develop towards high speed and high power density. The main component of the motor - the soft magnetic alloy core is the key to affecting the motor loss and efficiency. The currently used silicon steel soft magnetic alloy has difficulty reducing the core loss of high-speed motors. As the frequency increases further, the loss of silicon steel core will be greater, which will lead to a significant decrease in motor efficiency and even cause the motor to be difficult to run smoothly and overheat and damage. Therefore, it is of great significance to develop and adopt high-performance soft magnetic alloy materials to meet the needs of high-speed, high-frequency, and high-efficiency motors.

[0003] Breakthroughs in new technologies and product equipment often require the support of new high-performance materials. Iron-based amorphous materials stand out among all kinds of soft magnetic materials due to their excellent comprehensive soft magnetic properties. Iron-based amorphous alloys have a special atomic structure, with long-range disordered atomic arrangement and no grain boundaries to hinder the movement of magnetic domain walls, so they have smaller coercive force and low hysteresis loss; at the same time, the atoms are disordered and the electron free path is short, so iron-based amorphous alloys have greater resistivity and relatively smaller eddy current loss than crystalline alloys with the same composition.

[0004] Due to its excellent comprehensive soft magnetic properties, iron-based soft magnetic amorphous alloys have been used in the field of power electronics, such as amorphous motor stator cores, inductors, sensors, wireless charging, etc. However, there are still many problems and challenges in the research and development of iron-based soft magnetic amorphous alloys.

[0005] The Fe-based soft magnetic amorphous alloy system B that has been industrialized and applied in practice s The mainstream iron-based amorphous and nanocrystalline products on the market are still 1K101 (METGLAS2605SA1), and its B sOnly 1.56T. Most of the newly developed alloy components have not been put into practical use, mainly for the following reasons: First, the contradiction between high saturation magnetic induction intensity and strong amorphous forming ability is difficult to resolve. In iron-based amorphous alloys with strong amorphous forming ability, non-ferromagnetic elements such as Mo and Zr are generally added, which will greatly reduce the saturation magnetic induction intensity of the alloy. Avoiding the addition of non-ferromagnetic elements and increasing the content of ferromagnetic elements can effectively improve the saturation magnetic induction intensity. However, one-sided consideration of improving the saturation magnetic induction intensity will lead to too low amorphous forming ability of the alloy system, making its critical cooling rate exceed the cooling capacity of the existing industrial production of amorphous alloy strips, making it difficult to achieve large-scale production and application. In addition, the cost of some high saturation magnetic induction intensity amorphous soft magnetic alloys is too high. For example, the alloy with the brand name METGLAS2605Co developed by Allied-Signal Company in the United States, although its saturation magnetic induction intensity can reach 1.8T, due to the large amount of Co added, its cost increases sharply, making it difficult to promote on a large scale. Therefore, the development of new iron-based soft magnetic amorphous alloy components suitable for industrial production is still one of the hot spots.

[0006] In recent years, researchers have made a series of progress in the research and development of high-iron-content iron-based amorphous alloys. For example, in 2006, Ogawa et al. invented an iron-based amorphous alloy Fe HB1. 81.7 SiC 16 C 0.3 and Fe 82 SiC 14 C2, B s Reaching 1.64T and 1.67T respectively. However, the research is mainly concentrated in systems such as FeSiB, FeSiBP, FeSiBC, and FePC that contain only 2 or 3 metalloid elements besides Fe. There are relatively few amorphous alloys that contain four non-metallic elements: B, C, Si, and P. In the few research works containing four non-metallic elements, the carbon content is generally low and the Si content is high to improve the amorphous forming ability. And in a few five-component alloys containing FeSiBPC, the content of P element is usually high to improve the amorphous forming ability, but the addition of a large amount of P will significantly reduce the saturation magnetic induction intensity of the system.

[0007] The simultaneous addition of B, C, Si, and P can increase the disorder of the system and is expected to improve its amorphous forming ability. However, the interactions between the elements in the five-component FeSiBPC system are very complex. In order to obtain excellent amorphous forming ability and good soft magnetic properties, in-depth theoretical analysis is needed. Based on long-term theoretical and experimental research and research, this research group found that although the addition of P element is beneficial to reducing coercivity, it will also reduce the saturation magnetic induction intensity. C and B are beneficial to increase the saturation magnetic induction intensity to a certain extent. The atoms in amorphous alloys are arranged in a disordered manner, and their average atomic radius difference is directly related to the structure and amorphous forming ability. Studies have found that there is a positive correlation between the saturation magnetic induction intensity and the average atomic radius difference in amorphous alloys with high iron content. In addition, because the Si element has a large negative mixing heat with C, P, and B, it will affect the average atomic radius difference and the saturation magnetic induction intensity of the alloy. After initial research, this research group proposed the synergistic influence mechanism of Si, C, P, and B elements on the amorphous forming ability and soft magnetic properties of high iron content iron-based alloys. Under the conditions of appropriate Si, C, P, and B element contents, the traditional idea of ​​the influence of single elements on amorphous forming ability and soft magnetic properties was broken through, and based on the interaction and synergistic effect between elements, an iron-based amorphous alloy system with high amorphous forming ability and excellent soft magnetic properties was obtained. However, the coercivity of the iron-based amorphous alloy system is difficult to reduce to below 1A / m. After optimized annealing treatment, the coercivity is mostly concentrated in 2-7A / m, which still needs to be further reduced to reduce the loss during application; the amorphous synthesis ability also needs to be further improved. In addition, after structural relaxation and / or performance regulation annealing, the amorphous alloy becomes brittle, which has a significant adverse effect on the application of amorphous soft magnetic alloys. In the application of amorphous alloys, how to reduce the brittleness of amorphous soft magnetic alloy strips after annealing so that they maintain sufficient ductility has always been a difficulty in the amorphous field, but reducing the brittleness of amorphous alloy strips is very important for their subsequent processing and safe use of devices. Summary of the invention

[0008] Therefore, the technical problem to be solved by the present invention is to overcome the key problems in the prior art that the coercivity of iron-based amorphous alloys needs to be further reduced, and the saturation magnetic induction intensity, amorphous forming ability and ductility need to be improved. By studying the interaction and synergistic effect of elements, an iron-based amorphous alloy with low coercivity, high saturation magnetic induction intensity, high ductility and strong forming ability and a preparation method are provided.

[0009] To this end, the present invention provides the following technical solutions.

[0010] The present invention provides an iron-based amorphous alloy having low coercivity, high ductility and strong forming ability, having the general formula:

[0011] Fe a B b C c Sid P e M f ;

[0012] Wherein, a%, b%, c%, d%, e% and f% are the atomic percentages of each element;

[0013] M is V;

[0014] 0≤f≤0.8;

[0015] d>e;

[0016] 0.13≤b / a≤0.17;

[0017] d+e≤c; or, 4.0≤c+d+e≤5.0.

[0018] In the iron-based amorphous alloy, 80.2≤a≤83, 11.0≤b≤13.5, 1.8≤c≤3.5, 1.0≤d≤2.1, 0.3≤e≤1, and satisfies: 17≤b+c+d+e≤19.0, a+b+c+d+e+f=100.

[0019] In the iron-based amorphous alloy, c>d; 0.13≤e / c≤0.46; 14.4≤b+c≤16.

[0020] In the iron-based amorphous alloy, 81≤a≤83, 11.6≤b≤13.5, 2.2≤c≤3.4, and 1.2≤d≤2.1.

[0021] The preferred structural formula of the iron-based amorphous alloy is as follows:

[0022] Fe 81.4 B 13.2 C 2.8 Si 1.8 P 0.8 , Fe 81.8 B 12.8 C 2.8 Si 1.8 P 0.8 , Fe 82.2 B 12.4 C 2.8 Si 1.8 P 0.8 , Fe 82.6 B 12 C 2.8 Si 1.8 P 0.8 , Fe 83 B 11.6 C 2.8 Si 1.8 P 0.8 , Fe 82.2 B12.2 C3Si 1.8 P 0.8 、Fe 82.2 B 12 C 3.2 Si 1.8 P 0.8 、Fe 82.2 B 11.8 C 3.4 Si 1.8 P 0.8 、Fe 82.2 B 12.4 C3Si 1.8 P 0.6 、Fe 82.2 B 13 C 2.8 Si 1.2 P 0.8 、Fe 82.2 B 12.7 C 2.8 Si 1.5 P 0.8 、Fe 82.2 B 12.2 C 2.8 Si 2.1 P 0.7 、Fe 82 B 12.4 C 2.8 Si 1.8 P1、Fe 82.4 B 12 C 2.8 Si 1.8 P1、Fe 82.5 B 12.4 C 2.2 Si 1.8 P1、Fe 82.2 B 12.3 C 2.8 Si 2.1 P 0.6 、Fe 82.5 B 13.2 C 2.2 Si 1.8 P 0.3 、Fe 82.5 B 12.5 C 2.5 Si 1.8 P 0.7 或Fe 82.5 B 12.4 C 2.2 Si 1.8 V 0.6 P 0.6 。

[0023] The critical thickness of the iron-based amorphous alloy is not less than 30 μm.

[0024] The present invention also provides a method for preparing the above-mentioned iron-based amorphous alloy, comprising the following steps:

[0025] (1) Ingredients;

[0026] (2) smelting to obtain a master alloy;

[0027] (3) Producing an amorphous alloy.

[0028] In the preparation method, the step (2) further comprises a purification step after obtaining the master alloy;

[0029] Preferably, the purified medium comprises boron oxide;

[0030] Preferably, the purification is carried out under conditions 50-250K higher than the melting point of the master alloy.

[0031] In the preparation method, the step (3) adopts suction casting, spray casting, water quenching or single roller spinning to obtain the amorphous alloy.

[0032] In the preparation method, the step (3) adopts a single-roll spinning method to form the master alloy into a strip shape, and obtains an amorphous alloy strip after cooling;

[0033] Preferably, the cooling rate is 10 4 -10 6 K / s.

[0034] During melting, the vacuum degree is less than 5×10 -3 Pa;

[0035] In the purification step, the purification medium is placed under vacuum conditions (<5Pa) and kept warm at a temperature of 1200-1400K to remove moisture. When the purification medium is free of bubbles and moisture, the master alloy is placed in the purification medium for purification.

[0036] The specific steps of purification include: placing the master alloy in a purification medium and purifying it at a temperature 50-250K higher than the melting point of the master alloy, allowing the alloy melt to cool and solidify during the purification process, and then heating it up to melt and purify it, repeating the process until no bubbles are generated at the alloy interface when it is melted again and the interface is stable, thus completing the purification step.

[0037] The technical solution of the present invention has the following advantages:

[0038] 1. The present invention provides an iron-based amorphous alloy with low coercivity, high ductility and strong forming ability, and the iron-based amorphous alloy has the general formula: Fe a B b Cc Si d P e M f ; Wherein, a%, b%, c%, d%, e% and f% are the atomic percentages of each element; M is V; 0≤f≤0.8; d>e; 0.13≤b / a≤0.17; d+e≤c; or, 4.0≤c+d+e≤5.0. The saturation magnetic induction intensity of the iron-based amorphous alloy is ≥1.66T or the magnetic induction intensity B under the condition of 800A / m 800 ≥1.65T, the saturation magnetic flux density of some alloys is 1.69-1.7T, and some are 1.72-1.73T. The coercive force of the iron-based amorphous alloy after annealing is ≤1.0A / m, and the coercive force of some alloys can be as low as 0.4A / m; and the iron-based amorphous alloy also has a high amorphous forming ability (critical thickness can reach more than 85μm) and bending toughness (excellent performance of the amorphous alloy not being brittle after annealing). The iron-based amorphous alloy provided by the present invention is a FeBCSiP iron-based alloy system with high saturation magnetic flux density, low coercive force and low iron loss. The iron-based amorphous alloy does not contain precious metal elements, easily oxidized elements and high melting point elements, has low cost, low requirements for industrial equipment, and is conducive to industrial production.

[0039] 2. The iron-based amorphous alloy provided by the present invention, in the alloy system proposed by the present invention, has the outstanding feature that the C content in the iron-based amorphous alloy of the present invention is relatively high, so that the C content in the alloy is greater than the Si content and the P content, and the C content in the alloy is greater than or equal to the content of (Si+P) or (C+Si+P) is greater than or equal to 4.0at.% and less than or equal to 5.0at.%; at the same time, the (B+C) content is greater than or equal to 14.4at.%, and the ratio of the B element content to the Fe element content is greater than or equal to 0.13 and less than or equal to 0.17. Such alloy composition design is based on improving the total magnetic moment of Fe of the alloy. At the same time, the interaction and synergistic effects of B, Si, C, and P elements are integrated to improve the amorphous forming ability of the alloy, and ensure a reasonable melting point and amorphous strip forming performance. In addition, in the Fe-BC-Si-P quinary system, when the proportions of large atoms and small atoms match, the system is more likely to form a high stacking density, and the free volume is significantly reduced after annealing, thereby obtaining a lower coercive force. When the Fe content is relatively high and the proportion of metalloid elements is appropriate, the proportion of metal bonds between atoms is higher, and the proportion of anisotropic covalent bonds is relatively reduced, which can ensure the smooth increase of shear bands during deformation and prevent localized instability and fracture, thereby maintaining excellent toughness. Experimental results show that such an alloy design ensures high saturation magnetic induction intensity (up to 1.73T), low coercive force (minimum 0.4A / m) and strong amorphous forming ability (critical thickness can reach more than 85 microns), and the coercive force of most alloys is less than or equal to 1.0A / m. At the same time, most amorphous alloys have good bending toughness after structural relaxation annealing, that is, they have the excellent performance of non-brittle amorphous alloys after annealing. The iron-based amorphous alloy strip proposed by the present invention has excellent soft magnetic properties and good comprehensive properties, breaking through the problem that the coercive force of iron-based amorphous soft magnetic alloys is difficult to be less than or equal to 1.0A / m and annealing brittleness, and has good application prospects.

[0040] Through the reasonable composition ratio of Fe, B, C, Si and P, the alloy system has excellent comprehensive soft magnetic properties, the saturation magnetic induction intensity is ≥1.65T, and after further optimization of the magnetic field annealing process, the coercive force

[0041] ≤1.0A / m.

[0042] 3. The preparation method of the iron-based amorphous alloy provided by the present invention can form a completely amorphous strip with a critical thickness of ≥30μm by a single-roller spinning method, and the critical thickness of some preferred alloys can reach ≥85μm. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0044] Figure 1-3 is the X-ray diffraction pattern of the iron-based amorphous alloy of each embodiment and comparative example of the present invention;

[0045] Figure 4 is the thermodynamic parameter Curie temperature T of the iron-based amorphous alloy strip of each embodiment of the present invention. c and the initial crystallization temperature T x ;

[0046] Figure 5 is the critical thickness of the amorphous ribbon of Examples 1-3 and Example 6 of the present invention;

[0047] Figure 6 It is the microstructure of strips of different thicknesses in Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0048] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.

[0049] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0050] Example 1

[0051] This embodiment provides an iron-based amorphous alloy with low coercivity, high ductility and strong forming ability, and the structural formula is: Fe 81.4 B 13.2 C 2.8 Si 1.8 P 0.8 .

[0052] The method for preparing the above-mentioned iron-based amorphous alloy comprises the following steps:

[0053] The materials are prepared according to the composition of the iron-based amorphous alloy.

[0054] The raw materials are repeatedly smelted three times in a vacuum melting furnace to make the smelting uniform and to form a master alloy ingot.

[0055] The master alloy ingot was placed in an induction furnace for melting, and the strip was prepared by the copper wheel single-roller strip-swinging method. The alloy melt was sprayed through a nozzle of a certain shape onto a rotating copper roller with a linear speed of about 33m / s to prepare an alloy strip with a thickness of 30μm.

[0056] Example 2

[0057] This embodiment provides an iron-based amorphous alloy with low coercivity, high ductility and strong forming ability, and the structural formula is: Fe 81.8 B 12.8 C 2.8 Si 1.8 P 0.8 .

[0058] The preparation method of the above-mentioned iron-based amorphous alloy is the same as that of Example 1.

[0059] The thickness of the Fe-based amorphous alloy strip prepared in this embodiment is 30 μm.

[0060] Example 3

[0061] This embodiment provides an iron-based amorphous alloy with low coercivity, high ductility and strong forming ability, and the structural formula is: Fe 82.2 B 12.4 C 2.8 Si 1.8 P 0.8 .

[0062] The preparation method of the above-mentioned iron-based amorphous alloy is the same as that of Example 1.

[0063] The thickness of the Fe-based amorphous alloy strip prepared in this embodiment is 30 μm.

[0064] Example 4

[0065] This embodiment provides an iron-based amorphous alloy with low coercivity, high ductility and strong forming ability, and the structural formula is: Fe 82.6 B 12 C 2.8 Si 1.8 P 0.8 .

[0066] The difference between the above-mentioned method for preparing the iron-based amorphous alloy and Example 1 is that the line speed is 44 m / s, and the thickness of the iron-based amorphous alloy strip prepared in this example is 25 μm.

[0067] Example 5

[0068] This embodiment provides an iron-based amorphous alloy with low coercivity, high ductility and strong forming ability, and the structural formula is: Fe 83 B 11.6 C 2.8 Si 1.8 P 0.8 .

[0069] The preparation method of the above-mentioned iron-based amorphous alloy is the same as that of Example 4. The thickness of the iron-based amorphous alloy strip prepared in this example is 25 μm.

[0070] Example 6

[0071] This embodiment provides an iron-based amorphous alloy with low coercivity, high ductility and strong forming ability, and the structural formula is: Fe 82.2 B 12.2 C3Si 1.8 P 0.8 .

[0072] The difference between the above-mentioned method for preparing the iron-based amorphous alloy and Example 1 is that the line speed is 44 m / s, and the thickness of the iron-based amorphous alloy strip prepared in this example is 30 μm.

[0073] Example 7

[0074] This embodiment provides an iron-based amorphous alloy with low coercivity, high ductility and strong forming ability, and the structural formula is: Fe 82.2 B 12 C 3.2 Si 1.8 P 0.8 .

[0075] The preparation method of the above-mentioned iron-based amorphous alloy is the same as that of Example 1. The thickness of the iron-based amorphous alloy strip prepared in this example is 30 μm.

[0076] Example 8

[0077] This embodiment provides an iron-based amorphous alloy with low coercivity, high ductility and strong forming ability, and the structural formula is: Fe 82.2 B 11.8 C 3.4 Si 1.8 P 0.8 .

[0078] The preparation method of the above-mentioned iron-based amorphous alloy is the same as that of Example 1. The thickness of the iron-based amorphous alloy strip prepared in this example is 30 μm.

[0079] Example 9

[0080] This embodiment provides an iron-based amorphous alloy with low coercivity, high ductility and strong forming ability, and the structural formula is: Fe82.2 B 12.4 C3Si 1.8 P 0.6 .

[0081] The preparation method of the above-mentioned iron-based amorphous alloy is the same as that of Example 1. The thickness of the iron-based amorphous alloy strip prepared in this example is 30 μm.

[0082] Example 10

[0083] This embodiment provides an iron-based amorphous alloy with low coercivity, high ductility and strong forming ability, and the structural formula is: Fe 82.2 B 13 C 2.8 Si 1.2 P 0.8 .

[0084] The difference between the above-mentioned method for preparing the iron-based amorphous alloy and Example 1 is that the line speed is 44 m / s, and the thickness of the iron-based amorphous alloy strip prepared in this example is 20 μm.

[0085] Embodiment 11

[0086] This embodiment provides an iron-based amorphous alloy with low coercivity, high ductility and strong forming ability, and the structural formula is: Fe 82.2 B 12.7 C 2.8 Si 1.5 P 0.8 .

[0087] The difference between the above-mentioned method for preparing the iron-based amorphous alloy and Example 1 is that the line speed is 44 m / s, and the thickness of the iron-based amorphous alloy strip prepared in this example is 20 μm.

[0088] Example 12

[0089] This embodiment provides an iron-based amorphous alloy with low coercivity, high ductility and strong forming ability, and the structural formula is: Fe 82.2 B 12.2 C 2.8 Si 2.1 P 0.7 .

[0090] The difference between the above-mentioned method for preparing the iron-based amorphous alloy and Example 1 is that the line speed is 44 m / s, and the thickness of the iron-based amorphous alloy strip prepared in this example is 20 μm.

[0091] Example 13

[0092] This embodiment provides an iron-based amorphous alloy with low coercivity, high ductility and strong forming ability, and the structural formula is: Fe 82 B12.4 C 2.8 Si 1.8 P1.

[0093] The preparation method of the above-mentioned iron-based amorphous alloy is the same as that of Example 1. The thickness of the iron-based amorphous alloy strip prepared in this example is 30 μm.

[0094] Embodiment 14

[0095] This embodiment provides an iron-based amorphous alloy with low coercivity, high ductility and strong forming ability, and the structural formula is: Fe 82.4 B 12 C 2.8 Si 1.8 P1.

[0096] The preparation method of the above-mentioned iron-based amorphous alloy is the same as that of Example 1. The thickness of the iron-based amorphous alloy strip prepared in this example is 30 μm.

[0097] Embodiment 15

[0098] This embodiment provides an iron-based amorphous alloy with low coercivity, high ductility and strong forming ability, and the structural formula is: Fe 82.5 B 12.5 C 2.2 Si 1.8 P1.

[0099] The preparation method of the above-mentioned iron-based amorphous alloy is the same as that of Example 1. The thickness of the iron-based amorphous alloy strip prepared in this example is 30 μm.

[0100] Example 16

[0101] This embodiment provides an iron-based amorphous alloy with low coercivity, high ductility and strong forming ability, and the structural formula is: Fe 82.2 B 12.3 C 2.8 Si 2.1 P 0.6 .

[0102] The difference between the above-mentioned method for preparing the iron-based amorphous alloy and Example 1 is that the line speed is 44 m / s, and the thickness of the iron-based amorphous alloy strip prepared in this example is 20 μm.

[0103] Embodiment 17

[0104] This embodiment provides an iron-based amorphous alloy with low coercivity, high ductility and strong forming ability, and the structural formula is: Fe 82.5 B 13.2 C 2.2 Si 1.8 P 0.3 .

[0105] The difference between the above-mentioned method for preparing the iron-based amorphous alloy and Example 1 is that the line speed is 44 m / s, and the thickness of the iron-based amorphous alloy strip prepared in this example is 20 μm.

[0106] Embodiment 18

[0107] This embodiment provides an iron-based amorphous alloy with low coercivity, high ductility and strong forming ability, and the structural formula is: Fe 82.5 B 12.5 C 2.5 Si 1.8 P 0.7 .

[0108] The difference between the above-mentioned method for preparing the iron-based amorphous alloy and Example 1 is that the line speed is 44 m / s, and the thickness of the iron-based amorphous alloy strip prepared in this example is 20 μm.

[0109] Embodiment 19

[0110] This embodiment provides an iron-based amorphous alloy with low coercivity, high ductility and strong forming ability, and the structural formula is: Fe 82.4 B 12 C 2.8 Si 1.8 P 0.6 V 0.4 .

[0111] The difference between the above-mentioned method for preparing the iron-based amorphous alloy and Example 1 is that the line speed is 44 m / s, and the thickness of the iron-based amorphous alloy strip prepared in this example is 23 μm.

[0112] Comparative Example 1

[0113] This comparative example provides an iron-based amorphous alloy having a structural formula of Fe 84 B 10 C2Si2P2.

[0114] The preparation method of the above-mentioned iron-based amorphous alloy is the same as that of Example 1, and the results are shown in Table 1.

[0115] Test example

[0116] This test example provides the relevant properties of the iron-based amorphous alloys of various embodiments and comparative examples, as follows:

[0117] (1) The X-ray diffraction patterns of the Fe-based amorphous alloys of the embodiments and comparative examples are shown in Figure 1-3 ,from Figure 1-3It can be seen that the iron-based amorphous alloy in each embodiment has only one broadened slow diffraction peak and no sharp diffraction peak corresponding to an obvious crystal structure. The X-ray spectrum analysis results show that the iron-based amorphous alloy strip provided in each embodiment has an amorphous structure and no other crystalline phase, indicating that the strip is an amorphous alloy strip.

[0118] (2) Thermodynamic parameters Curie temperature T of the iron-based amorphous alloy strips of each embodiment and comparative example were obtained by differential scanning calorimetry (DSC). c and the initial crystallization temperature T x , the results are shown in Figure 4 and Table 1.

[0119] (3) The magnetic properties of the iron-based amorphous alloy strips of each embodiment and comparative example 1 were tested, and the results are shown in Table 1. Magnetic induction intensity B 800 and coercivity H c It is the performance of the Fe-based amorphous alloy after isothermal annealing. The corresponding isothermal annealing parameters are shown in Table 1; saturation magnetic induction intensity B s Tested using a vibrating sample magnetometer (VSM); B 800 The test was conducted using a BH hysteresis loop instrument. As can be seen from Table 1, the Fe-based amorphous alloy obtained in the embodiment of the present invention has high saturation magnetic induction intensity and low coercive force.

[0120] (4) By adjusting the linear speed of the copper roller during the melt spinning process to change the cooling rate, alloy strips of different thicknesses were obtained. The microstructures of the strips of different thicknesses were characterized by XRD to obtain the critical thickness of the amorphous strips of each embodiment. The results are shown in Figure 5 The critical thickness of the amorphous strips in Examples 1-3 and 6 is not less than 85 μm, 75 μm, 75 μm, and 47 μm, respectively; the corresponding linear speeds of the copper rollers are 9 m / s, 10 m / s, 10 m / s, and 16 m / s, respectively. This indicates that the critical thickness of the iron-based amorphous alloy strip provided by the present invention can be optimally higher than 85 μm.

[0121] (5) In T C -50℃~T xThe alloy strips obtained in Example 3, Example 4, Example 5, Example 6, Example 7, Example 8, Example 9, Example 10, Example 11, Example 12, Example 16, Example 17, and Example 18 were subjected to isothermal annealing treatment within the range of -100°C. The temperature and time of the annealing treatment are shown in Table 1. Then, the toughness of the annealed amorphous strips was tested. The testing device consisted of a screw micrometer (with an accuracy of 0.001 mm) and two quartz plates. The testing method was as follows: first, the strip thickness was measured, which was recorded as t; the strip was bent into a U shape and placed between two flat plates, with the free surface of the strip on the outside; then, the screw micrometer was rotated to bring the two flat plates closer at a rate of 0.1 mm / s until the strip broke or was completely bent. At this time, the distance between the flat plates was recorded as 2γ; then, the relative fracture bending strain λ of the alloy strip was t / (2γ-t). To ensure the reliability of the experiment, at least three bending tests were performed, and the average value of the three tests was taken as the fracture toughness. When the strip can be bent 180° without breaking, 2γ=2t, and λ=1. The test results show that the alloy strips obtained in Example 3, Example 4, Example 5, Example 6, Example 7, Example 8, Example 9, Example 10, Example 11, Example 12, Example 16, Example 17, and Example 18 have a bending angle of 180° and a bending angle of 180°. C -50℃~T x After isothermal annealing in the range of -100°C, the toughness ensures that the strip can be folded 180° without breaking, that is, λ=1. This is very beneficial for industrial applications. Compared with λ=0.077 obtained in Comparative Example 1, the λ of the amorphous alloy strip obtained in the embodiment is higher, and the toughness of the amorphous strip in the comparative example is significantly lower than that of the amorphous strip obtained in the present invention.

[0122] (6) Regarding Comparative Example 1. When characterizing the amorphous forming ability of the iron-based amorphous alloy of the comparative example, the preparation method is the same as that of Example 1 to obtain an iron-based amorphous alloy strip. By adjusting the corresponding parameters (including the copper roller speed, the injection pressure, etc.) during the melt spinning process to change the cooling rate, alloy strips with thicknesses of 22 μm and 30 μm are obtained. The microstructures of the strips with different thicknesses are characterized by XRD. Figure 6 . When the strip thickness is 22μm, there is only one broadened diffuse diffraction peak in the XRD spectrum, and there is no sharp diffraction peak corresponding to the obvious crystal structure. The X-ray diffraction spectrum analysis results show that the sample has an amorphous structure and no other crystalline phases, which indicates that the strip is an amorphous alloy strip. When the strip thickness is 30μm, a diffraction peak corresponding to the crystalline α-Fe phase appears near 2θ=65° in the XRD spectrum, indicating that the strip has been crystallized and is not a completely amorphous alloy strip. The above XRD results show that the critical thickness of the amorphous strip of this composition (that is, the maximum thickness of the completely amorphous strip) is between 22 and 30μm. After isothermal annealing at 330℃ for 15min, the relative fracture bending strain λ of the alloy strip is 0.077.

[0123] Table 1 Performance results of iron-based alloys in various embodiments and comparative examples

[0124]

[0125] Note: The blank space in the table indicates that the data has not been tested. The magnetic induction intensity in Examples 10, 11, 12, 16, 17, and 18 has not been tested because the measured B 800 The capacity is greater than or equal to 1.65T.

[0126] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the scope of protection of the invention.

Claims

1. An iron-based amorphous alloy having low coercivity, high ductility and strong forming ability, characterized in that: With the general formula: Fe a B b C c Si d P e M f ; Wherein, a%, b%, c%, d%, e% and f% are the atomic percentages of each element; M is V; 0≤f≤0.8; d>e; 0.13≤b / a≤0.17; d+e≤c; or, 4.0≤c+d+e≤5.

0.

2. The iron-based amorphous alloy according to claim 1, characterized in that: 80.2≤a≤83, 11.0≤b≤13.5, 1.8≤c≤3.5, 1.0≤d≤2.1, 0.3≤e≤1, and satisfies: 17≤b+c+d+e≤19.0, a+b+c+d+e+f=100.

3. The iron-based amorphous alloy according to claim 1 or 2, characterized in that: c>d; 0.13≤e / c≤0.46; 14.4≤b+c≤16.

4. The iron-based amorphous alloy according to any one of claims 1 to 3, characterized in that: 81≤a≤83, 11.6≤b≤13.5, 2.2≤c≤3.4, 1.2≤d≤2.

1.

5. The iron-based amorphous alloy according to any one of claims 1 to 4, characterized in that: The preferred structural formula is as follows: Fe 81.4 B 13.2 C 2.8 Si 1.8 P 0.8 、Fe 81.8 B 12.8 C 2.8 Si 1.8 P 0.8 、Fe 82.2 B 12.4 C 2.8 Si 1.8 P 0.8 、Fe 82.6 B 12 C 2.8 Si 1.8 P 0.8 、Fe 83 B 11.6 C 2.8 Si 1.8 P 0.8 、Fe 82.2 B 12.2 C3Si 1.8 P 0.8 、Fe 82.2 B 12 C 3.2 Si 1.8 P 0.8 、Fe 82.2 B 11.8 C 3.4 Si 1.8 P 0.8 、Fe 82.2 B 12.4 C3Si 1.8 P 0.6 、Fe 82.2 B 13 C 2.8 Si 1.2 P 0.8 、Fe 82.2 B 12.7 C 2.8 Si 1.5 P 0.8 、Fe 82.2 B 12.2 C 2.8 Si 2.1 P 0.7 、Fe 82 B 12.4 C 2.8 Si 1.8 P1、Fe 82.4 B 12 C 2.8 Si 1.8 P1、Fe 825 B 124 C 22 Si 18 P1, Fe 822 B 123 C 28 Si 21 P 06 , Fe 825 B 132 C 22 Si 18 P 03 , Fe 82.5 B 12.5 C 2.5 Si 1.8 P 0.7 or Fe 82.5 B 12.4 C 2.2 Si 1.8 V 0.6 P 0.6 .

6. The iron-based amorphous alloy according to any one of claims 1 to 5, characterized in that: The critical thickness of the iron-based amorphous alloy is not less than 30 μm.

7. A method for preparing the iron-based amorphous alloy according to any one of claims 1 to 6, characterized in that: The following steps are involved: (1) Ingredients; (2) smelting to obtain a master alloy; (3) Producing an amorphous alloy.

8. The preparation method according to claim 7, characterized in that: The step (2) further comprises a purification step after obtaining the master alloy; Preferably, the purified medium comprises boron oxide; Preferably, the purification is carried out under conditions 50-250K higher than the melting point of the master alloy.

9. The preparation method according to claim 7 or 8, characterized in that: In the step (3), the amorphous alloy is obtained by suction casting, spray casting, water quenching or single roller spinning quenching.

10. The preparation method according to any one of claims 7 to 9, characterized in that: In the step (3), a single-roll spinning method is used to form the master alloy into a strip shape, and an amorphous alloy strip is obtained after cooling; Preferably, the cooling rate is 10 4 -10 6 K / s.